A VENDOR-BUYER OPTIMAL CONSIGNMENT POLICY FOR A SEASONAL PRODUCT WITH UNIFORM DISTRIBUTION OF DEMAND - Islam, S. M. S.; Hoque, M. A. (Malaysian Journal of Science, 2014)
Use of seasonal products is common in our life. Control of management cost of these products plays an important role in delivering them to customers with reasonable prices and profit. Some research has been carried out with uniform distribution of demands to maximize profit independently for the vendor and the buyer, and also for the integrated system by considering shortage cost and inventory cost of the unsold items. In the latter system the vendor is liable for shipment, and bears financial holding cost by keeping items in the buyer’s warehouse but retains the ownership, and the buyer bears only the operational holding cost. To make a fruitful consignment agreement, the vendor guarantees the buyer to earn at least as much as in traditional policy by offering the buyer an extra incentive along with the agreed commission. However, warehouse capacity, transport cost and inventory cost during processing of a product and meeting demand are essential in this system. To make the available models more realistic, this study extends them including these factors. New solution techniques to the extended models are developed, and the effects of the included factors are highlighted by comparative studies on the results of numerical problems. Keywords: Consignment policy; Traditional policy; Newsboy problem; Inventory; Transport